Improvement of polydopamine-loaded salidroside on osseointegration of titanium implants - Qingqing Yi; Pengchen Liang; Dongyu Liang; Liou Cao; Shuang Sha; Xinquan Jiang; Qing Chang (BMC, 2022)
Abstract Background Microarc oxidation (MAO) on the surface of medical pure titanium can improve its histocompatibility, and loading drugs on the surface can resist excessive intimal hyperplasia. Methods In this study, salidroside (SAL) was loaded on the surface of porous titanium (Ti) with polydopamine (PDA) carrier. The effects of SAL on the osteogenesis and angiogenesis of Ti implants were studied by phalloidin staining, alizarin red staining, ALP staining, wound-healing assay, cell transwell assay, matrigel tube formation, and osteogenic and angiogenic genes and proteins expression detected by PCR and western blot in vitro. The bone defect model experiments in rats was established in vivo including X-ray, micro CT, hematoxylin and eosin staining (HE), immunohistochemistry (IHC), Goldner's trichrome analysis, Safranin O-fast green staining and determination of contents of TNF-α and IL-6 in serum. Results EDS and EDS mapping showed that SAL could be loaded on the surface of the MAO coating by PDA. A drug release experiment showed that SAL loaded on the Ti coating could release slowly and stably without sudden release risk. In vitro cell experiments showed that the SAL coating could promote the proliferation, morphology, calcification and alkaline phosphate activity of MC3T3-E1 cells. At the same time, it promoted the migration and tube formation of HUVEC cells. The SAL coating promoted osteogenesis and angiogenesis by promoting the expression of genes and proteins related to. In vivo experiments, HE and IHC showed that SAL significantly promoted the expression of COL-1 and CD31. Goldner's trichrome and Safranin O-fast green staining showed that SAL coating could increase the new bone tissue around the implantation site. The SAL coating had anti-inflammatory activity by reducing the levels of TNF-α and IL-6 in vivo. Conclusion Therefore, SAL could improve osteogenesis and angiogenesis in conjunction with the Ti-PDA coating.